Adding Intelligence to Cars Using the Neural Knowledge DNA. Issue 3 (3rd April 2017) - Zhang, Haoxi; Li, Fei; Wang, Juan; Wang, Zuli; Shi, Lei; Zhao, Jun; Sanín, Cesar; Szczerbicki, Edward
ABSTRACT: In this paper, we propose a Neural Knowledge DNA (NK-DNA)-based framework that is capable of learning from the car's daily operations and reusing such learned knowledge in future tasks. The NK-DNA is a novel knowledge representation and reasoning approach designed to support discovering, storing, reusing, improving, and sharing knowledge among machines and computing devices. We examine our framework for drivers' classification based on their driving behaviors. The experimental data are collected via smartphone sensors. The initial results are presented, and the direction for our future research is defined.